Molecular identification and DNA barcoding of Chaenomeles japonica in Pakistan - Mohammad Islam; Sajjad Sajjad; Yehia Hazzazi; Mari Sumayli; Suad Alruzayza; Khushi Muhammad; Sajidul UI Ghafoor; Tufail Muhammad; Inamullah Ullah; A. El-Shabasy (PLoS ONE, 2026)
Chaenomeles japonica (Thunb.) Lindl., an ornamental species belonging to the family Rosaceae, was molecularly identified from a cultivated population in the Hazara region, Khyber Pakhtunkhwa (KP), Pakistan. Fresh leaf samples were collected from a cultivated garden, and genomic DNA was extracted for molecular analysis. Four chloroplast DNA markers ( matK, rbcLa, trn A , and ycf3 ) were amplified and sequenced. PCR amplification showed a 100% success rate, generating sequence lengths ranging from 400–1600 bp depending on the marker. BLAST analysis revealed 99–100% sequence identity, 100% query coverage, and E-values of 0.0 when compared with reference sequences available in GenBank, primarily from China, Japan, and the United States. Phylogenetic analysis using Neighbour Joining method demonstrated that the obtained sequences clustered with authenticated Chaenomeles japonica accessions, supported by bootstrap values. The results confirm the molecular identity of cultivated C. japonica in Pakistan and highlight the utility of chloroplast DNA barcoding markers for accurate species identification of ornamental plants.